Optimizing Data Input Process To Improve System Reliability in pt.big Warehouse Management - Carolina, Aura; N , Rusdi Hidayat (Business and Investment Review, 2025)
Efficient and accurate data input process is very important to improve system reliability in warehouse management. This article discusses strategies to optimize the data input process at PT.BIG, with a focus on the application of information technology and employee training. This study uses a qualitative approach that aims to identify challenges in the data input process, the application of information technology, employee training, an effective monitoring system that can improve the accuracy and efficiency of data input, and provide solutions that can improve the accuracy and reliability of the system. The results of the study indicate that the implementation of a technology-based warehouse management system and appropriate training can reduce data input errors, speed up operational processes, and increase customer satisfaction.